The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1172/jci108804
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Chronic Renal Failure

Abstract: A B S T R A C T Thyroid function was evaluated in 46patients with end-stage kidney disease and 42 normal subjects. Patients were studied before and after the institution of maintenance hemodialysis (HD) and after renal transplantation (RT). Serum total triiodothyronine concentrations (TT3, ng/100 ml, mean± SD) were 63±17 and 83±22 in the non-HD and HD groups, respectively. Values from normal subjects were 128±25 and from RT patients 134±20. The TT3 was in the hypothyroid range (<78 ng/100 ml; 2 SD below normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(47 citation statements)
references
References 48 publications
3
42
0
1
Order By: Relevance
“…The T3 PR was markedly reduced in our patients, which is a feature common to other nonthyroidal illnesses (6)(7)(8). T3 production could be reduced as a result of decreased free T4 availability or to impaired enzymatic deiodination of T4.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…The T3 PR was markedly reduced in our patients, which is a feature common to other nonthyroidal illnesses (6)(7)(8). T3 production could be reduced as a result of decreased free T4 availability or to impaired enzymatic deiodination of T4.…”
Section: Resultssupporting
confidence: 50%
“…roxine (TT4)' in association with normal serum thyrotropin (TSH) levels (1)(2)(3)(4)(5). In addition, total serum triiodothyronine (TT3) levels are decreased, and total reverse T3 (TrT3) values are usually increased (1, [3][4][5], as in other nonthyroidal illnesses (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In the human being, nonthyroidal illness results in marked alterations in thyroid hormone concentrations and binding to serum proteins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Many patients with a variety of nonthyroidal disorders have normal circulating L-thyroxine (T4)' with an increase in free T4.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the decrease in serum T3 and FT3-I, and variable changes in serum T4 and FT4-I, serum TSH and the TSH response to TRH have been normal in most reports of patients with nonthyroidal diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, Bermudez et al (3) showed that a small increase in the TSH response to TRH occurred in sick patients with decreased serum T3as compared with similar patients with serum T3 in the normal range; and Burroughs et al (11) reported that the TSH response to TRH was blunted in about one-third of euthyroid geriatric patients with a variety of nonthyroidal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Changes occur frequently in peripheral thyroid hormone metabolism and in results of tests of thyroid function in patients with acute and chronic nonthyroidal diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Characteristic laboratory data in such patients include normal to slightly decreased serum thyroxine (T4)l concentration and decreased serum T4 binding.…”
Section: Introductionmentioning
confidence: 99%